MANAJEMEN KERJA SAMA SEKOLAH MENENGAH KEJURUAN DENGAN INDUSTRI DAN DUNIA KERJA - Amrullah, Abdullathif Karim; Susatya, Edhy; Biddinika, Muhammad Kunta (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2025)
Vocational high school education is more effective and efficient if vocational high schools and industries closely. In fact, it is not easy for vocational high schools to obtain cooperation partners with industry and the world of work, the cooperation relationship certainly does not just happen without going through a long process. This study aims to analyze the management of vocational high school cooperation with industry and the world of work including planning, implementation, and evaluation of cooperation. The results show that cooperation planning is based on; (1) potential mapping, (2) regulations, (3) objectives, (4) urgency, and (5) cooperation strategies. The implementation of cooperation is based on; (1) exploration, (2) communication and coordination, (3) forms of activities, and (4) stakeholder involvement in cooperation. Evaluation of cooperation is based on; (1) monitoring and evaluation, (3) activity reporting, (4) supporting factors, (5) inhibiting factors, (6) efforts to overcome obstacles, (7) goal achievement, (8) benefits, and (9) cooperation development. Supporting factors for vocational high school cooperation with industry and the world of work are in the form of positive support that is effectively communicated by all related parties in carrying out commitments to achieve common goals. Factors inhibiting cooperation in the form of a negative mindset and lack of awareness of harmony in achieving common goals. Efforts to overcome obstacles to cooperation in the form of increasing awareness of commitment to achieving common goals with open dialog using the principles of coordination and effective communication that is collaborative. ABSTRAKPendidikan SMK lebih efektif dan efisien apabila SMK dengan IDUKA melakukan kerja sama yang erat. Kenyataanya tidak mudah bagi SMK untuk memperoleh mitra kerja sama dengan IDUKA, hubungan kerja sama tentu tidak terjadi begitu saja tanpa melalui proses panjang. Penelitian ini bertujuan menganalisis manajemen kerja sama SMK dengan IDUKA meliputi perencanaan, pelaksanaan, dan evaluasi kerja sama. Hasil penelitian menunjukan perencanaan kerja sama didasarkan pada; (1) pemetaan potensi, (2) peraturan, (3) tujuan, (4) urgensi, dan (5) strategi kerja sama. Pelaksanaan kerja sama didasarkan pada; (1) penjajakan, (2) komunikasi dan koordinasi, (3) bentuk kegiatan, dan (4) keterlibatan stakeholder dalam bekerja sama. Evaluasi kerja sama didasarkan pada; (1) monitoring dan evaluasi, (3) pelaporan kegiatan, (4) faktor pendukung, (5) faktor penghambat, (6) upaya mengatasi hambatan, (7) ketercapaian tujuan, (8) manfaat, dan (9) pengembangan kerja sama. Faktor pendukung kerja sama SMK dengan IDUKA berupa dukungan positif yang dikomunikasikan efektif seluruh pihak terkait dalam menjalankan komitmen untuk mencapai tujuan bersama. Faktor penghambat kerja sama berupa mindset negatif dan kurangnya kesadaran terhadap keselarsan dalam mencapai tujuan bersama. Upaya mengatasi hambatan kerja sama berupa meningkatkan kesadaran komitmen untuk mencapai tujuan bersama dengan dialog terbuka menggunakan prinsip koordinasi dan komunikasi efektif yang bersifat kolaboratif.